Pengembangan Usaha UMKM Melalui Inovasi Varian Rasa Lumpia Ubi Ungu “Ungu Munchies” - Dini Febriani; Nor Fadhilatur Rohma; Aisyah Armysta Putri; Anisa Septia Mahardiani; Fidan Achmad Prastyo; Tri Wahjoedi; Nindya Kartika Kusmayati (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The objective of this project is to provide culinary innovation support for purple sweet potato spring rolls to develop the “Ungu Munchies” MSME. This program, which focuses on improving business capabilities through regional culinary innovation, uses descriptive qualitative techniques, through in-depth interviews, direct observation, and documentation. Three flavor variants—chocolate, melted Prochiz cheese, and mozzarella—were created as innovations. Based on consumer trials, the melted Prochiz cheese and chocolate variants were rated best in terms of taste, texture, and aesthetic appeal. Compared to traditional purple sweet potato spring rolls, the flavor innovations have been shown to increase purchase intention and product differentiation while adding value. Product legitimacy is further strengthened by business legality in the form of a Business Identification Number (NIB) and Halal certification. In addition, strategies supporting MSMEs through flavor experimentation, product development, and digital marketing tactics enhance their ability to compete in the contemporary market. This project demonstrates that the development of culinary MSMEs can benefit from product innovation based on local foods.